End-User Computing Satisfaction on Digital Trade Facilitation in the Philippines - Romer C. Castillo; Heizel P. De Villa; Emmanuel C. Encinas; Jesserey Joyce D. Hernandez; Marvic M. Mandocdoc (Journal of Innovation Information Technology and Application (JINITA), 2022)
Digital trade facilitation is increasingly becoming essential in a modern customs environment. Many countries have started computerizing and automating their trade procedures, the success of which depends upon their government’s information technology development. In usability perspective, the most appropriate success measure of an information system is the end-users’ satisfaction. This study assessed the end-user computing satisfaction (EUCS) on digital trade facilitation in the Philippines, known as electronic to mobile (e2m) system. This also determined the profile of e2m clients and the differences on their satisfaction. This further established correlations among the dimensions of EUCS. The study is a descriptive-survey research, which used a valid and reliable EUCS questionnaire. The respondents consisted of 49 e2m clients who were selected conveniently. Statistical tests employed were Mann-Whitney U-Test, Kruskal-Wallis H-Test, and Spearman’s Correlation. Results showed that majority of respondents are customs brokers, most are 4-6 years in profession, and with more than 10 transactions in a month. The end-users were generally satisfied on the total EUCS, as well as in content, accuracy, and timeliness, while they were very satisfied in format, and ease of use. Results also revealed that there are significant differences on clients’ satisfaction on format when grouped to profession, on ease of use when grouped to years in profession, and on accuracy and total EUCS when grouped to number of transactions in a month. All the five EUCS dimensions have significant positive moderate to strong correlations with each other.